Unbalanced Strength Exercises Using Designed Tools and Their Effects on Some Biomechanical Variables in Young 110m Hurdles - Rashe, Antsar; Ramadan, Shokan; Arkan, Zeina (Journal of Physical Education, 2018)
Unbalanced Strength Exercises Using Designed Tools and Their Effects on Some Biomechanical Variables in Young 110m Hurdles The problem of the research lies in the low level of motor performance during passing the hurdle in young hurdlers. The research aimed at designing training divided for unbalanced strength as well as designing exercises for this type of strength to identify their effect on some biomechanical variables in young 110m hurdles. The subjects were ( 8) elite 110m hurdlers. The researchers conducted one test, 110m hurdles test, and calculated the biomechanical variables. The exercises were applied for ten weeks with three training sessions per week. The data was collected and treated using proper statistical operations to conclude that the exercises using designed tools have great effect on working muscles as well as on physical abilities and biomechanical variables.